2018
DOI: 10.1111/echo.13852
|View full text |Cite
|
Sign up to set email alerts
|

The right ventricular outflow tract in pediatric pulmonary hypertension—Data from the European Pediatric Pulmonary Vascular Disease Network

Abstract: In pediatric PH cohort, the RVOT VTI is decreased, and the TRV/RVOT VTI ratio and the RVOT diameter increased compared to healthy subjects. Assessment of RVOT variables, together with established RV parameters, allows for a comprehensive assessment of global right heart size and performance in children with PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…3 We recently published a consensus statement on the diagnosis and treatment of pediatric PH, 2 normative PAAT reference values in 756 infants and children, 3 and abnormalities in PAAT in pediatric patients with PH. 3 The study by Levy et al 1 contributes to the current literature knowledge [2][3][4][5][6][7] and emphasizes that echocardiographic parameters, such as PAAT, RV outlet tract diameter, and speckle-tracking echocardiography-derived strain parameters, have significant value for the noninvasive assessment of RV function and pulmonary blood flow in all infants born preterm at 1 year corrected age, irrespective of a diagnosis of BPD or late PH. The study also shows that infants born preterm exhibit characteristics of PVD at 1 year corrected age, regardless of neonatal lung disease status.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…3 We recently published a consensus statement on the diagnosis and treatment of pediatric PH, 2 normative PAAT reference values in 756 infants and children, 3 and abnormalities in PAAT in pediatric patients with PH. 3 The study by Levy et al 1 contributes to the current literature knowledge [2][3][4][5][6][7] and emphasizes that echocardiographic parameters, such as PAAT, RV outlet tract diameter, and speckle-tracking echocardiography-derived strain parameters, have significant value for the noninvasive assessment of RV function and pulmonary blood flow in all infants born preterm at 1 year corrected age, irrespective of a diagnosis of BPD or late PH. The study also shows that infants born preterm exhibit characteristics of PVD at 1 year corrected age, regardless of neonatal lung disease status.…”
Section: To the Editormentioning
confidence: 99%
“…5 Studies have also shown that for a heart rate <60 bpm or >100 bpm, the PAAT needed to be corrected for heart rate to improve correlation. 6,7 We not only adjusted for the heart rate with the ratio of PAAT/RVET, but also established validated equations that show good relationships with invasive measures of RV afterload in children and infants with heart rates ranging between 55 and 150 bpm. 5 We support the idea that the high variability of agedependent growth mandates exploration of z-scores that index measurements to age, body surface area, body length, body weight, or heart rate.…”
Section: To the Editormentioning
confidence: 99%
“…Echocardiographic measurements of the pulmonary artery acceleration time (PAAT; also known as “time to peak velocity”), and the relation of the PAAT to the right ventricular ejection time (ET) are increasingly used to assess the pulmonary artery pressure (PAP) in infants, children and adults with PH [ 10 , 11 , 12 , 13 ]. In this context, a shorter PAAT and a lower PAAT:ET ratio are indicative of increased pulmonary artery pressure (PAP) [ 12 , 14 ]. The prognostic role of PAAT:ET values in CDH neonates is not well investigated [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%